Analysis of milk-borne public health risks in milk markets in Kenya - Omore, Amos O.; Arimi, S.M.; Kang'ethe, Erastus K.; McDermott, John J.; Staal, Steven J. (International Livestock Research Institute, 2002)
The major role played by informal milk markets in Kenya and the benefits to those associated with it are now widely acknowledged. The benefits include higher prices for farmers, income generation for the market agents and convenient delivery and lower prices for poor consumers. However, in spite of these benefits, regulations governing informal marketing of milk continue to be unfavourable and do not reflect local realities of milk marketing, having been based on models derived from industrialised countries where virtually all milk destined for the market is pasteurised and packaged.